56.2k views
4 votes
Solve for yyy. -3 = 7\left(y-\dfrac97\right)−3=7(y− 7 9 ​ )minus, 3, equals, 7, left parenthesis, y, minus, start fraction, 9, divided by, 7, end fraction, right parenthesis

User Bladimir
by
4.6k points

1 Answer

2 votes

Answer:

y = 6/7

Explanation:

The equation given is:

-3 = 7(y - 9/7)

To solve this, we will expand the bracket and afterwards, collect like terms:

-3 = (7*y) - (9/7 * 7)

-3 = 7y - 9

Collecting numeric terms to the left hand side:

-3 + 9 = 7y

=> 6 = 7y

=> y = 6/7

That is the solution.

User Kwame
by
5.1k points